2011
DOI: 10.1002/stem.615
|View full text |Cite
|
Sign up to set email alerts
|

LacdiNAc (GalNAcβ1-4GlcNAc) Contributes to Self-Renewal of Mouse Embryonic Stem Cells by Regulating Leukemia Inhibitory Factor/STAT3 Signaling

Abstract: Self-renewal of mouse embryonic stem cells (mESCs) is maintained by leukemia inhibitory factor (LIF)/signal transducer and activator of transcription (STAT3) signaling. However, this signaling control does not function in neither mouse epiblast stem cells (mEpiSCs) nor human ESCs (hESCs) or human induced pluripotent stem cells (hiPSCs). To date, the underlying molecular mechanisms that determine this differential LIF-responsiveness have not been clarified. Here, we show that the cell surface glycan LacdiNAc (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 54 publications
1
43
0
Order By: Relevance
“…We found that B4GALNT3 knockdown decreased LacdiNAc expression of several glycoproteins by biotinylated WFA blotting (Figure 2A, lower penal). OCT4 and NANOG are stem cell associated markers and knockdown of B4GALNT3 suppressed its expression in mouse embryonic stem cells [13]. We therefore investigate whether the expression of OCT4 and NANOG alters in B4GALNT3 knockdown cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that B4GALNT3 knockdown decreased LacdiNAc expression of several glycoproteins by biotinylated WFA blotting (Figure 2A, lower penal). OCT4 and NANOG are stem cell associated markers and knockdown of B4GALNT3 suppressed its expression in mouse embryonic stem cells [13]. We therefore investigate whether the expression of OCT4 and NANOG alters in B4GALNT3 knockdown cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, the underlying mechanisms are still unclear. A recent study showed increased LacdiNAc expression enhances self-renewal of mouse embryonic stem cells and B4GALNT3 knockdown decreases the expression of LacdiNAc [13]. We therefore hypothesized that B4GALNT3 could enhance the cancer stem-like cell property in colorectal cancer.…”
Section: Introductionmentioning
confidence: 98%
“…GalNAc␤1-3GlcNAc is a linkage isomer of LacdiNAc (N,NЈ-diacetyllactosediamine, GalNAc␤1-4GlcNAc) found in the N-glycans of glycoproteins such as lutropin (a hormone produced by gonadotroph cells) and tenascin-R (an extracellular matrix exclusively expressed in the central nervous system) as well as in glycoproteins from parasites (40,41). The LacdiNAc structure in the leukemia inhibitory factor receptor is known to influence self-renewal maintenance of mouse embryonic stem cells (42). Considering that LnbX does not act on LacdiNAc␤-pNP and that GalNAc␤1-3GlcNAc␤-pNP hydrolysis is not inhibited by the presence of LacdiNAc␤-pNP, the enzyme may serve as a new tool for examining the glycan structures of glycoconjugates and for distinguishing between GalNAc␤1-3-GlcNAc and LacdiNAc structures.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has demonstrated the involvement of LacdiNAc in the self-renewal of mouse embryonic stem cells by regulating LIF/STAT3 signaling (42). Undifferentiated state mouse embryonic stem cells expressed LacdiNAc at higher levels than differentiated state cells, and expression of the glycan on the LIF receptor (gp130) was shown to be required for the stable colocalization of the receptor with lipid raft/caveolar proteins, such as caveolin-1, and for the transduction of a sufficiently strong LIF/STAT3 signal.…”
Section: Glycosylated (N-or O-linked)mentioning
confidence: 99%